Global relationships among energy, environmental and macroeconomic variables with income and regional considerations - Agiakloglou, Christos; Gkouvakis, Michael (Energy Economics Letters, 2025)
This study investigates relationships between energy, environmental, agricultural and macroeconomic variables for 43 countries taking also into consideration income and regional effects. The aim of this research is to investigate the overall attitude of these countries towards energy consumption, economic growth and the environment at a global level, a result that could play an important role for policy recommendations for each country under its particular characteristics. Panel data estimations techniques along with Granger causality, cointegration tests and error correction models are used to extract meaningful results from the data, while data are split based on countries’ income (High income versus Medium and Low income) and countries’ region (Africa, Asia, America and Europe). The results show that the relationships of these variables alter according to the data formation, especially under income categorization, while under regional categorization agricultural and forest variables play a dominant role in the economic activity of each region supporting also long-term relationships with energy and macroeconomic variables. These results can raise awareness for different policy recommendations on the environment, as it seems that it is important to consider the overall growth stage of the country and not just the region to which it belongs.